Improving attending rounds: Qualitative reflections from multidisciplinary providers. Issue 3 (September 2015) - Najafi, Nader; Monash, Bradley; Mourad, Michelle; Ding, Yile; Glass, Marcia; Burrell, Gregory J.; Harrison, James D.
Abstract: Background. Attending rounds, the time for the attending physician and the team to discuss the team's patients, take place at teaching hospitals every day, often with little standardization. Objective. This hypothesis-generating qualitative study sought to solicit improvement recommendations for standardizing attending rounds from the perspective of a multi-disciplinary group of providers. Methods. Attending physicians, housestaff (residents and interns), medical students, nurses and pharmacists at an academic medical center participated in a quality improvement initiative between January and April 2013. Participants completed an individual or focus group interview or an e-mail survey with three open-ended questions: (1) What are poor or ineffective practices for attending rounds? (2) How would you change attending rounds structure and function? (3) What do you consider best practices for attending rounds? We undertook content analysis to summarize each clinical stakeholder group's improvement recommendations. Results. Sixty stakeholders participated in our study including 23 attending hospitalists, 24 housestaff, 7 medical students, 2 pharmacists and 4 nurses. Key improvement recommendations included (1) performing a pre-rounds huddle, (2) planning of the visit schedule based on illness or pending discharge, (3) real-time order writing, (4) patient involvement in rounds with shared decision-making, (5) bedside nurse inclusion and (6) minimizing interruption of intern or student presentations. Conclusions. The practice improvement recommendations identified in this study will require deliberate systems changes and training to implement, and they warrant rigorous evaluation to determine their impact on the clinical and educational goals of rounds.